2019
DOI: 10.2139/ssrn.3455952
|View full text |Cite
|
Sign up to set email alerts
|

Water, Sanitation and Agriculture Linkages With Health and Nutrition Improvement

Abstract: have greatly supported the researchers during the design phase of the field research and in providing comments, logistical support and diagrammatic illustrations for the research output. Four detailed doctoral dissertations developed by the co-authors at ZEF form part of the background material of this study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 106 publications
(179 reference statements)
0
1
0
Order By: Relevance
“…Previous studies have found that agricultural programmes, preventative health care (e.g., bednets), and environmental quality have heterogeneous (i.e., differential) effects on health in developing countries (Pan & Singhal, 2019;Okyere, 2020b) due to differences in biological and resource composition. Furthermore, previous studies address the effects of irrigation on a subset of household members, for instance, children (see, e.g., Klinkenberg et al, 2005;Gerber et al 2019;Okyere & Usman, 2021 5 ). We argue that these studies do not present the complete evidence on the potential effects of irrigation on health.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have found that agricultural programmes, preventative health care (e.g., bednets), and environmental quality have heterogeneous (i.e., differential) effects on health in developing countries (Pan & Singhal, 2019;Okyere, 2020b) due to differences in biological and resource composition. Furthermore, previous studies address the effects of irrigation on a subset of household members, for instance, children (see, e.g., Klinkenberg et al, 2005;Gerber et al 2019;Okyere & Usman, 2021 5 ). We argue that these studies do not present the complete evidence on the potential effects of irrigation on health.…”
Section: Introductionmentioning
confidence: 99%